Factors Influencing Brand Switching in Telecommunication Industry in Sri Lanka: A Study Based on Undergraduates in Sri Lanka. - Wimalasiri, R. K. H. S. (8th International Conference on Business & Information ICBI – 2017, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2017)
Telecommunication industry is an industry which is with fierce competition. This intense competition leads to reduce the market share of mobile service providers in terms of customers. Hence this study is conducted with the purpose of identifying the factors influence the youngsters to move from one brand to another in the telecommunication industry in Sri Lanka. This research was conducted as a cross-sectional survey, and utilized sample frame was undergraduates of university of Kelaniya Sri Lanka. Including Commerce and Management, Science and Arts, 300 undergraduates were captured random sampling method from those faculties as sample subjects and the data were collected by means of a structured questionnaire and the validation is tested under Cronbach alpha test. Multiple regression analysis is used as the key analysis tool to this study after satisfying the required assumptions. The core finding of the study is switching cost and services having a significant impact on brand switching. Promotion factor does not have a significant impact on brand switching. Previous researchers have used various services provided by the mobile service providers as separate independent variables in different conceptual models in many studies.
Keywords: Brand switching; Promotions; Switching Cost; Telecommunication; Undergraduates